A Woman with Double Intra Uterine Device: A Case Report - Işık Gönenç; Zeynep Tuzcular Vural; Nurettin Aka; Can Ertuğrul Tüfekçi; Gültekin Köse (Medical Network, 2016)
A 30-year-old woman, who applied to our family planning unit with her plain urinary system radiogram showing two T -shaped intrauterine devices within the pelvic region, is presented. The patient's medical history revealed that a copper-T intra uterine device (IUD) had been inserted ten years ago, and that she had a normal vaginal delivery seven years after, when she was informed by her physician that her IUD had been expelled and she conceived afterwards. No further attempts were made to confirm its presence. Since it was assumed that the IUD had fallen out, another copper-T IUD was inserted six weeks after her delivery. She only complained of a mild increase in her menstrual flow and mild dismenorrhea. It was due to her urinary tract symptoms that a plain radiogram of the urinary system was planned by the urology clinic and then she was referred to our family planning unit after the presentation of the double IUDs. We find it very important to stress the management of patients with pregnancies after IUD insertions and to make sure if the IUD remained within the uterine cavity even after pregnancy termination or delivery, as it usually takes little effort to diagnose their presences with a plain radiogram and ultrasonography.